Effects of pancreatic denervation on secretion of pancreatic hormones in rats (Annals of Medical Research, 2023)
Aim: The aim of this study was to determine whether expermentaly pancreatic denervation (PD) injury caused effects on pancreatic tissue and endocrine secretions.Materials and Methods: A total of 50 adult male Wistar Albino rats (8 weeks old, 280-300 g) were randomly divided into five groups (n=10) as Control, Sham acute, PD acute, Sham chronic, PD chronic. The PD procedure was performed by cutting the pancreatic vagal and splenic nerves. Sham acute and PD acute groups were sacrificed 120 minutes after the PD procedure, while Control, Sham chronic, and PD chronic groups were sacrificed 7 days after the PD procedure. Pancreatic tissues were collected after the rats were sacrificed. Tissue samples were homogenized, and insulin, glucagon and norepinephrine levels were measured using commercial ELISA kits. Statistical analysis of the data was conducted using the Bonferroni-corrected Mann-Whitney U test in the IBM SPSS Statistics 24.0 Windows program.Results: The decrease in norepinephrine level of pancreas tissue was found to be significant PD groups compared to Control and Sham groups. The decrease of glucagon and insulin level was found to be significant in PD acute and PD cronic compared to Contol and Sham groups.Conclusion: According to our findings, pancreatic denervation short and long term effects were effective in insulin and glucagon secretion in the model which examined in pancreatic denervation groups.
Keywords: Brain; Pancreatic denervation; Pancreas; Insulin; Glucagon; Norepinephrine